Changes in fungal community composition of biofilms on limestone across a chronosequence in Campeche, Mexico - Gómez-Cornelio, Sergio; Ortega-Morales, Otto; Morón-Ríos, Alejandro; Reyes-Estebanez, Manuela; de la Rosa-García, Susana (Instituto de Ecología, A.C., 2016)
Background and Aims: The colonization of lithic substrates by fungal communities is determined by the properties of the substrate (bioreceptivity) and climatic and microclimatic conditions. However, the effect of the exposure time of the limestone surface to the environment on fungal communities has not been extensively investigated. In this study, we analyze the composition and structure of fungal communities occurring in biofilms on limestone walls of modern edifications constructed at different times in a subtropical environment in Campeche, Mexico.Methods: A chronosequence of walls built one, five and 10 years ago was considered. On each wall, three surface areas of 3 × 3 cm of the corresponding biofilm were scraped for subsequent analysis. Fungi were isolated by washing and particle filtration technique and were then inoculated in two contrasting culture media (oligotrophic and copiotrophic). The fungi were identified according to macro and microscopic characteristics.Key results: We found 73 genera and 202 species from 844 isolates. Our results showed that fungal communities differed in each biofilm. In the middle-aged biofilm a high number of isolates was found, but both species richness and diversity were low. In contrast, in the old biofilm species richness and diversity were high; Hyphomycete 1, Myrothecium roridum and Pestalotiopsis maculans were abundant. The dominant species in the middle-aged biofilm were Curvularia lunata, Curvularia pallescens, Fusarium oxysporum and Fusarium redolens, and in the young biofilm were Cladosporium cladosporioides, Curvularia clavata, Paraconiothyrium sp. and Phoma eupyrena.Conclusions: Our results suggest that the composition of the fungal community in each biofilm varies according to time of exposure to the environment. Furthermore, the fungal community was composed of a pool of uncommon species that might be autochthonous to limestone.